Net Protein Requirements for Maintenance and Weight gain in Male Guinea Pigs (Cavia porcellus) of the Peru Breed - Tapie Canacuan, William Armando; Posada-Ochoa, Sandra Lucia; Rosero-Noguera, Jaime Ricardo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
Net protein requirements for weight gain (NPg) and maintenance (NPm) in meat-producing guinea pigs are not yet established. The objective of this study was to estimate the requirements for NPm and NPg in male guinea pigs of the Peru breed using the comparative slaughter method. Sixty guinea pigs with an initial body weight (BW) of 393 ± 55 g were distributed in five groups of 12 animals. The animals were fed a pelleted diet. At the beginning of the experiment, a reference group with a BW 385.9 ± 44.5 g was slaughtered. Two groups were fed ad libitum, another group received 75% of the feed provided to the ad libitum groups, and a fifth group was kept at the maintenance level. One of the ad libitum-fed groups was slaughtered when its BW reached 846.6 ± 48 g. The other animals, distributed according to their feeding level, were slaughtered when the second ad libitum-fed group reached 1197 ± 84 g BW. The NPm requirement was 3.97 g/kg/EBW0.75 (empty body weight). And the requirement was NPg 2.5 g/kg EBW0.75. The protein use efficiency was 0.629. Highlights: The net protein requirement for weight gain in guinea pigs is 2.5 g/kg EBW75/day. The net protein requirement for maintenance in guinea pigs is 3.7 g/kg EBW75/day. The protein utilization efficiency is 0.629. The endogenous and metabolic nitrogen losses in guinea pigs are 0.6359 g/kg EBW75/day.